OPTIMIZATION OF HUMAN RESOURCE PERFORMANCE THROUGH BEHAVIORAL AND ENVIRONMENTAL APPROACHES - Abdara Mumtahanah Coto; Khoirul Attiq (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2026)
PURPOSE - This research aims to analyze the influence of competence and work environment on employee performance by considering the role of work discipline as a mediator.METHODOLOGY - The method used in this research is a quantitative method with a sampling technique using sensus sampling and 100 employees were obtained from PT. Genco Furniture Indonesia as research respondents. Primary data was obtained through the distribution of questionnaires to respondents and processing the data using SEM-PLS analysis with SmartPLS 4 data processing program.FINDING - The results of this research reveal that competence directly has a positive and significant influence on employee performance, as well as a positive and significant influence on work discipline. Apart from that, the work environment also shows a positive and significant influence on employee performance, and a positive and significant influence on work discipline. Work discipline itself has been proven to have a positive and significant influence on employee performance. Furthermore, this research shows that indirectly, competence has a positive and significant influence on employee performance through work discipline, as well as the work environment which has a positive and significant influence on employee performance through work discipline.